IMPLEMENTASI PEMBELAJARAN BERBASIS GAULGA SEPALAM (GAME ULAR TANGGA SEPUTAR PENGETAHUAN AGAMA ISLAM) DI TPA SALAFIAH - Fitria Noviastuti; Faola Arina; Adi Putra Pratama; Arif Kurniawan; Rizki Aji Pangestu; Atha Mahdiyah Salma Putri; Ahmad Nugroho Santoso; Diaz Rizka Maulana Zein; Muhammad Anugrah Utama Djaya Prawira; Ghina Zahira Bima Shofa; Tri Puji Rahayu (Jendela Inovasi Daerah, 2026)
Islamic Religious Education for early childhood requires engaging and interactive methods to enhance students’ understanding and learning motivation. At TPA Salafiah in Dusun Candi, Desa Sidomulyo, Kabupaten Magelang, the learning process is still dominated by conventional lecture methods, causing students to become passive and easily bored. This study aims to improve students’ understanding of Islamic teachings and their motivation to learn the Qur’an through the innovation of a learning medium called Gaulga Sepalam, an educational snakes-and-ladders game based on Islamic materials. This study employed a Community Based Research (CBR) method consisting of planning, implementation, and evaluation stages. The subjects were 28 students of TPA Salafiah. Data were collected through observation, documentation, and recording of game results, while data analysis used a descriptive quantitative approach. The results showed an increase in student attendance from an average of 15 students to 25 students, representing a 66.7% improvement. In addition, increased religious understanding was indicated by sticker achievements, where 21 out of 28 students (75%) obtained more than 20 stickers at the end of the session. In conclusion, the implementation of the Gaulga Sepalam game-based learning media proved effective in improving students’ understanding of Islamic knowledge and their learning motivation at TPA Salafiah.